Computational fluid dynamics software based on the artificial compressibility method - Yosua Heru Irawan; Daru Sugati; Kristian Hubra Kadu; Syed Ahmad Raza (University of Muhammadiyah Malang, 2025)
This study aims to develop a computational fluid dynamics (CFD) software package based on the Artificial Compressibility Method (ACM) for solving incompressible fluid flow problems. CFD is a vital engineering tool that enables numerical simulation of fluid motion. The ACM, introduced to enhance computational efficiency, allows incompressible flows to be simulated similarly to compressible flows, resulting in faster and more stable numerical convergence. The Finite Volume Method (FVM) was employed to discretize the Navier–Stokes and continuity equations, incorporating an artificial compressibility term. The developed software was validated using two benchmark cases: lid-driven cavity flow and channel flow. In the lid-driven cavity flow test, simulations were conducted at Reynolds numbers (Re) of 100 and 3200, showing excellent agreement with benchmark data from Ghia et al. (1982). For the channel flow case, numerical results were compared with the analytical Hagen–Poiseuille solution for fully developed laminar flow, demonstrating strong consistency. The results indicate that the software accurately reproduces velocity profiles in both laminar and fully developed regimes, while also improving computational speed without compromising accuracy. This development broadens access to CFD technology for a wide range of engineering applications, enabling complex flow analyses with more efficient use of computational resources.